Practical Experience in the Application of Energy Roofs, Ground Heat Storages, and Active Thermal Protection on Experimental Buildings - Daniel Kalús; Daniela Koudelková; Veronika Mučková; Martin Sokol; Mária Kurčová; Peter Janík (Applied Sciences, 2022)
Research Area: Building components with integrated energy-active elements (BCEAE) are generally referred to as combined building-energy systems (CBES). Aim: Research on the application of energy (solar) roofs (ESR), ground heat storage (GHS), active thermal protection (ATP), and their cooperation in different modes of operation of energy systems with an emphasis on the use of renewable energy sources (RES) and waste heat. Methodology: The analysis and synthesis of the state of the art in the field, the inductive and analogical form of the creation of an innovative method of operation of combined building-energy systems, the development of an innovative solution of the envelope panel with integrated energy-active elements, the synthesis of the knowledge obtained from the scientific analysis and the transformation of the data into the design and implementation of the prototype of the prefabricated house IDA I and the experimental house EB2020. Results: The theoretical analysis of building structures with active thermal protection results in the determination of their energy potential and functionality, e.g., thermal barrier, heating/cooling, heat storage, etc. New technical solutions for envelopes with controlled heat transfer were proposed based on the implementation of experimental buildings. Conclusions: The novelty of our research lies in the design of different variants of the way of operation of energy systems using RES and in upgrading building envelope panels with integrated energy-active elements.